PWM based solar charge controller using IoT - H Ravishankar Kamath, Dr; S P M Sharma B, S; Siva Brahmaiah Rama, V (International Journal of Engineering and Technology, 2018)
IoT has numerous applications; in which one of them is solar power tracking and modulating network. Energy saving mechanism can be delineated in IoT, which can lessen both energy dissipation and human endeavor necessary to do the task. The proposed system has been rendered to accord the PWM based solar charge controller and its response by utilizing webservers and the laptops/cell phones. The gadget has been used is W5100, the web server which will be accumulated on W5100 module is employed as an IoT platform. As webservers are unconstrained of platforms, they can be adoptable in cell phones/ laptop which is instructed by the relays and sequentially webservers compute the solar charge controllers through W5100 module. The proposed system deals with solar power tracking and sends the information to laptop/cell phone with the help of web servers for energy lessening. The proposed system is capable of identifying the battery charging conditions under different circumstances whenever needed and can be further upgraded to track other utensils. There are diverse modules utilized in solar charge controller circuit which makes it as an IoT based device like Arduino Ethernet shield (W5100), Atmega328p, solar panel, battery, which is hugely cost-effective and also low energy utilization. [1].